Comparing the impact of vocational rehabilitation and the employment of persons with disabilities on companies: Analysis of existing research - Boris Miethlich (CER Comparative European Research, Proceedings of the 10th International Scientific Conference for Ph.D. students of EU countries, London, 29.-31.10.2018, 2018)
The constant above-average unemployment rate of people with disabilities (PWD) and the failure of government measures to date indicate the need for companies to address this issue themselves. A reliable understanding of the effects and implications of employment of PWD and vocational rehabilitation for strategic corporate management is therefore required to specifically promote the integration of PWD into the labor market. This paper compares the impacts of the two concepts from a management perspective. A literature review was conducted to collect and analyze the state of research for similarities and differences regarding the categories government policies, corporate social responsibility (CSR), benefits and consequences for companies and business opportunities using a summary content analysis. The results suggest that the effects on companies and the resulting implications are identical, at least over a longer period. The employment of PWD, as well as vocational rehabilitation, can be a key to attracting customers with disabilities and thus allowing to enter new market segments. – – Die weiterhin überdurchschnittliche Arbeitslosenquote von Menschen mit Behinderungen (PWD) sowie die bisherige Erfolglosigkeit staatlicher Massnahmen sprechen für die Notwendigkeit, dass dieses Anliegen durch Unternehmen selbst angesprochen werden muss. Für die gezielte Förderung der Integration von PWD in den Arbeitsmarkt ist daher ein reliables Verständnis der Auswirkungen und deren Implikationen der Beschäftigung von PWD und der beruflichen Rehabilitation für die strategische Unternehmensführung erforderlich. Diese Untersuchung vergleicht die Auswirkungen der beiden Konzepte aus Management Sicht. Anhand einer Literaturrecherche wird der Forschungsstand erhoben und mittels zusammenfassender Inhaltsanalyse auf Gemeinsamkeiten und Unterschiede in Bezug auf die Kategorien gesetzliche Vorgaben, soziale Unternehmensverantwortung, Vorteile und Konsequenzen für Unternehmen sowie Geschäftschancen analysiert. Die Ergebnisse legen die Schlussfolgerung nahe, dass die Auswirkungen auf Unternehmen und die daraus entstehenden Implikationen, mindestens über einen längeren Zeitraum betrachtet, identisch sind. Die Beschäftigung von PWD als auch die berufliche Rehabilitation können ein Schlüssel sein, um auch Kunden mit Behinderungen zu gewinnen und somit neue Marktsegmente zu erschliessen.
Keywords: J14; M14; 330; vocational rehabilitation; employment of persons with disabilities; CSR; strategic management